The Effect of Service Quality, Facilities, and Price on Guest Satisfaction at COMO Uma Canggu - Ni Kadek Yolan Oktania; I Wayan Ruspendi Junaedi; Ni Putu Dyah Krismawintari (LPPM Universitas Dhyana Pura, 2026)
The hospitality industry in Bali, especially in Canggu, is growing rapidly, resulting in increasingly fierce competition among star-rated hotels. As a five-star hotel, COMO Uma Canggu is required to maintain guest satisfaction through service, facilities, and competitive prices. This research aims to analyze the influence of service quality, facilities, and price on guest satisfaction at COMO UMA Canggu Hotel. The research subjects are hotel guests, with a sample size of 90 respondents determined using the Ferdinand formula. Data collection was carried out through the distribution of Likert-scale questionnaires. The data obtained were analyzed using multiple linear regression, with hypothesis testing performed using F-tests and t-tests at a significance level of 0.05. The analysis results showed that, partially, the variables of service quality, facilities, and price had a positive and significant effect on guest satisfaction. With a calculated t-value of 2.502 and a significance level of 0.037 (< 0.05), for facilities, the calculated t-value is 2.367 with a significance level of 0.020 (< 0.05), and for prices, the calculated t-value is 4.217 with a significance level of 0.001 (< 0.05). Simultaneously, these three variables also have a positive and significant effect on guest satisfaction, supported by an F-value of 9.565 and a significance level of 0.000 (< 0.05). The adjusted R² value of 82.4% indicates that guest satisfaction can be explained by the three independent variables, while the remaining 17.6% is influenced by other factors outside the model. This study contributes to the development of customer satisfaction literature in the hospitality industry and provides input for Hotel COMO Uma Canggu in improving its services, facilities, and pricing strategies to strengthen its competitiveness and guest satisfaction.